2004
DOI: 10.1017/s0022112004000151
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustics of hot jets

Abstract: A systematic study has been undertaken to quantify the effect of jet temperature on the noise radiated by subsonic jets. Nozzles of different diameters were tested to uncover the effects of Reynolds number. All the tests were carried out at Boeing's Low Speed Aeroacoustic Facility, with simultaneous measurement of thrust and noise. It is concluded that the change in spectral shape at high jet temperatures, normally attributed to the contribution from dipoles, is due to Reynolds number effects and not dipoles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
184
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(194 citation statements)
references
References 19 publications
10
184
0
Order By: Relevance
“…The decomposed field is found to follow the model spectrum in the pertinent range of acoustic frequencies and indicates a peak at approximately St ∼ 0.2. This is qualitatively consistent with far-field experimental supersonic jet data at similar Mach numbers (Seiner et al 1992;Viswanathan 2004;Tam et al 2008). A similar narrow-band character has also been observed in the near field of near-sonic jet LES .…”
Section: Properties Of the Decomposed Fieldssupporting
confidence: 89%
“…The decomposed field is found to follow the model spectrum in the pertinent range of acoustic frequencies and indicates a peak at approximately St ∼ 0.2. This is qualitatively consistent with far-field experimental supersonic jet data at similar Mach numbers (Seiner et al 1992;Viswanathan 2004;Tam et al 2008). A similar narrow-band character has also been observed in the near field of near-sonic jet LES .…”
Section: Properties Of the Decomposed Fieldssupporting
confidence: 89%
“…If the data confirms to previous evidence [32,37] in which the above suggestion found support, then the measured spectra of the current subsonic jet should fit Tam's FSS and LSS. This is examined by comparing the measured spectra to the LSS and FSS spectra of Tam as shown in Fig.…”
Section: Acoustic Far Field Resultssupporting
confidence: 84%
“…Tam & Burton [31], Tam et al [32] and later on Viswanathan [37] proposed a mechanism by which an acoustic wave may be radiated in a subsonic jet with features similar to Mach wave radiation. The proposed mechanism involves recognising the importance of amplitude modulation of instability waves.…”
Section: Acoustic Far Field Resultsmentioning
confidence: 99%
“…The effect of temperature on jet noise has been widely investigated experimentally (Tanna, 1977;Tanna et al, 1975;Viswanathan, 2004). It has been observed that, for a fixed acoustic Mach number M a = U j /c 0 , where c 0 is the sound velocity at ambient temperature, the radiated noise directly depends on the jet temperature.…”
Section: Temperature Effectmentioning
confidence: 99%